Trends And Patterns of Maternal Referrals from Ciawi Community Health Center To Referral Facilities In 2024 - Anastasya, Prischa; Prudencia, Fairy (Panakeia Journal of Epidemiology, 2025)
Maternal referral is a vital component of maternal healthcare systems, particularly at the primary care level such as community health centers (Puskesmas). This study aims to analyze the trends and referral patterns of maternal cases from Puskesmas Ciawi to higher-level healthcare facilities throughout the year 2024. The method used is descriptive quantitative research based on secondary data collected from monthly records of childbirth services (partus) and referral forms for pregnant and laboring mothers. Analysis focuses on the number of deliveries and referrals per month, the most common medical indications, and the frequently referred-to facilities. The results show monthly fluctuations in maternal referrals, with the highest peak in December. The number of referrals does not always correlate with the number of births, suggesting that clinical risks are the main drivers of referral decisions. The most frequent diagnoses include preeclampsia, premature rupture of membranes (PROM), obstructed labor, and antepartum hemorrhage. Most patients were referred to RSUD Ciawi as the primary network hospital. The study also found that BPJS (National Health Insurance) covered the majority of deliveries and referrals, highlighting its essential role in facilitating maternal care access. In conclusion, the maternal referral system at Puskesmas Ciawi functions fairly effectively, although strengthening the referral network, logistics, and staff capacity remains necessary. Recommendations include periodic evaluation of the referral system, regular training for healthcare workers, and the optimization of technology-based referral coordination.